Global overview on advances in structural health monitoring platforms - Mesquita, E. (2016)
Advances in the development of sensors, data processing systems, and numerical models have motivated the implementation of structural health monitoring (SHM) specially focused on the assessment of structural safety. Thus, this work presents a literature review about SHM platforms, especially from 1993 to 2015. In this way, a short history review about the recent advances on SHM, mainly related with dynamic monitoring, was summarized, and a benchmark and the main guidelines related with SHM platforms were also included in this review. Some case studies are also described here. Special attention was given to SHM platforms, and a method for their classification (an extension of Rytter's method) is presented. In addition, experiences related with heritage constructions, specially focused on maintenance, were included in this work. In the final section, some observations are made about the new prospects for SHM. The recent advances on SHM platforms contributed to the development of adaptive systems and to the cost reduction of the monitoring systems implementation, allowing the increase of its application in real structures. However, the monitoring systems should be implemented, optimizing all the available sensing technologies.